Effects of price discount on consumers’ perceptions of savings, quality, and value for apparel products: mediating effect of price discount affect - Jung Eun Lee; Jessie H. Chen-Yu (Fashion and Textiles, 2018)
Abstract Extending the price–quality–value model (Monroe and Krishnan in The perception of merchandise and store quality 209–232, 1985) and means-end model (Zeithaml in J Mark 52:2–22, 1988), we developed a conceptual model to investigate the mediating role of price discount affect (feeling aroused by price discounts) in the relationship between price discounts and consumers’ perceptions (perceived savings, quality, and value) and in the relationship between perceived value and purchase intentions in the context of online apparel products. A between-subject experimental design with four levels of price discounts (10, 30, 50, and 70%) was used. Jeans were selected as the product stimulus. Web pages were developed to create a fictional online store and to collect data. A total of 209 usable responses were collected by a research firm in the United States, and structural equation modeling was performed to analyze the data. The results showed that price discount affect played an important mediating role in the relationship between price discounts and consumers’ perceptions. When the direct effect of price discounts on perceived quality was examined, consumers perceived the apparel product with higher discounts as lower quality (i.e., a negative direct relationship). However, when price discount affect served as a mediator, the feelings created by a price discount led to a positive perception of product quality (i.e., a positive indirect relationship). By considering the influence of price discount affect, our model provides a better understanding of the effect of price discounts on consumers’ perceptions of apparel products.